One Health Approach to Arbovirus Control in Africa: Interests, Challenges, and Difficulties - (:unkn) unknown (My University, 2023)
The "One Health" concept considers that human and animal health, and ecosystems are closely related and aims to make a link between ecology and human and veterinary medicine. Due to the explosion in population growth along with the geographic and climatic conditions (equatorial and/or tropical climate), Africa is becoming a major hotspot for various socio-health issues associated with infectious diseases, including arboviruses. The incontestable advantages of a One Health approach in Africa lie in the fight against pathogens, such as arboviruses, and in the preservation of environmental, animal, and human health to ensure that the increasing high needs of this population are met as well as their protection against potential epidemics. The One Health strategy gives us a glimpse of the difficulties and challenges that the African continent faces. The importance of this approach in Africa is to establish guidelines and strategies for effective solutions and changes in behavior and harmful activities. Overall, the establishment of high-quality global health policies in the framework of the global health standards program would provide healthy and sustainable human-animal-environmental interactions for the welfare of all.
Keywords: African Research